2021
DOI: 10.1002/jsfa.11040
|View full text |Cite
|
Sign up to set email alerts
|

Brewing rich 2‐phenylethanol beer from cassava and its producing metabolisms in yeast

Abstract: BACKGROUND Cassava is rich in nutrition and has high edible value, but the development of the cassava industry is limited by the traditional low added value processing and utilization mode. In this study, cassava tuber was used as beer adjunct to develop a complete set of fermentation technology for manufacturing cassava beer. RESULTS The activities of transaminase, phenylpyruvate decarboxylase and dehydrogenase in 2‐phenylethanol Ehrlich biosynthesis pathway of Saccharomyces cerevisiae were higher in cassava … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Also higher alcohols play a crucial role in the flavour of beer. Of particular importance is 2phenylethanol characterised as possessing "rose flavour" [43]. In line with previous studies [5], the highest content of 2-phenylethanol was in the industrial beers (sample H and I), which made them have a better fragrance, taste and rose like aroma.…”
Section: Volatile Compounds Identificationsupporting
confidence: 85%
“…Also higher alcohols play a crucial role in the flavour of beer. Of particular importance is 2phenylethanol characterised as possessing "rose flavour" [43]. In line with previous studies [5], the highest content of 2-phenylethanol was in the industrial beers (sample H and I), which made them have a better fragrance, taste and rose like aroma.…”
Section: Volatile Compounds Identificationsupporting
confidence: 85%
“…This could be attributed to the fact that the enzymatic activities of PPYAT are activated by oxygen under aerobic conditions, and vice versa. Previous study have demonstrated that the activity of PPYAT could be influenced by different substances; for example, its activity on S. cerevisiae was higher in cassava beer than in malt beer ( 51 ). However, there are few studies investigating the enzymatic activity of PPYAT in aerobic and anaerobic environments.…”
Section: Resultsmentioning
confidence: 99%
“…in malt beer (51). However, there are few studies investigating the enzymatic activity of PPYAT in aerobic and anaerobic environments.…”
Section: Regulation Of Amino Acid Biosynthesismentioning
confidence: 99%
“…Following the methods reported by Li et al [24], the alcohol content, relative density, and original extraction of beer samples were determined according to the Chinese beer standard GB/T 4928-2008.…”
Section: Alcohol Content Relative Density and Original Extraction Of ...mentioning
confidence: 99%